KAJIAN HUKUM INTERNASIONAL TENTANG PERAN NORTH ATLANTIC TREATY ORGANIZATION (NATO) DALAM OPERASI PERDAMAIAN DI TIMUR TENGAH (STUDI KASUS: LIBYA) - Evelyne Theresia; Ningrum Natasya; Sutiarnoto Sutiarnoto (Journal of USU International Law, 2013)
ABSTRAK The peace process in the various Arab countries is still the world spotlight until now. Usually the conflict that often occurs between Arab countries is to end the leadership of an authoritarian state because it has served for decades, one of which is Libya (Muammar Gaddafi as head of state for 43 years). NATO as an international organization in the field of security played a role in the settlement of the conflict in Libya. The participation of NATO towards peace mediator Arab countries, it has many other important missions for the internal purposes of NATO. Israel (pro-Western) has always been the core issue of the state (pro-Arab) others. However, Gaddafi who issued an ultimatum to attack the U.S. and its allies to make Libya a target attack western countries (Article V of the NATO Treaty). NATO attacked Libya on grounds of violation of human rights in accordance with the UN Security Council. 1970 and 1973 Articles 39, 41 and 42 which further aggravate the situation. Article 33, which contains about 2 ways of resolving disputes should be taken by NATO. Libya is now having problems after the incident that Gaddafi elections, minimize violence and promoting human rights in order to build a democratic state and national unity.